2011
DOI: 10.1111/j.1473-2165.2011.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a new hyaluronic acid dermal filler in the treatment of severe nasolabial lines - 6-month interim results of a randomized, evaluator-blinded, intra-individual comparison study

Abstract: The new HA filler HA(E) provides better efficacy and similar local tolerability compared with HA(P) 6 months after the treatment of severe NLF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 13 publications
3
35
0
Order By: Relevance
“…Similar to previously reported interim data, 7 HA ED was noninferior to HA PER in terms of mean change from baseline in WSRS score at 6 months after the baseline treatment. At this time point, the mean between-treatment difference (HA PER − HA ED ) was 0.24, and the 95% CI ranged between 0.10 and 0.37 (i.e., above the predetermined margin [−0.5]).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Similar to previously reported interim data, 7 HA ED was noninferior to HA PER in terms of mean change from baseline in WSRS score at 6 months after the baseline treatment. At this time point, the mean between-treatment difference (HA PER − HA ED ) was 0.24, and the 95% CI ranged between 0.10 and 0.37 (i.e., above the predetermined margin [−0.5]).…”
Section: Resultssupporting
confidence: 89%
“…7 Here, the final effectiveness and safety outcomes up to 12 months after the baseline treatment were reported, thereby extending the published literature on product duration and safety for HA ED in comparison with a well-established HA filler (HA PER ) that has a similar intended use. This is also the first long-term study of HA ED , and the first long-term comparison of these two products for the treatment of severe NLFs.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The authors have concluded that, in addition to subjective assessment methods, a quantitative analysis is recommended using more objective methods to minimize the interrater variability [20]. In a recent study, Shin et al [2] and Asher et al [6] reported subjective assessment by blinded investigators of the efficacy of a dextran filler and different forms of hyaluronic acid on the correction of nasolabial folds. Finally, Brandt and collaborators have used the WSRS to assess facial wrinkles treated with hyaluronic acid but they have not specified if the evaluators were blinded [5].…”
Section: Wrinkle Severity Rating Scale (Wsrs)mentioning
confidence: 98%
“…Mild injection site reactions Treatment related [76] Prospective study (n = 60), 6 months follow-up ‡ Short term complications erythema, edema/swelling, bruising, pruritus, pain, tenderness Treatment related [77] Prospective study (n = ? ), 6 months follow-up…”
Section: Hyaluronic Acid (Cross-linked)mentioning
confidence: 99%